2007
DOI: 10.1158/0008-5472.can-07-1314
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium perfringens Enterotoxin as a Novel-Targeted Therapeutic for Brain Metastasis

Abstract: Brain metastasis is the most commonly occurring intracranial tumor whose incidence seems to be increasing. With standard therapy, the average survival time of patients is f8 months, and treatment often leads to neurologic dysfunction in longterm survivors, emphasizing the need for novel therapeutics. Clostridium perfringens enterotoxin (CPE) has recently been shown to rapidly and specifically destroy cancer cells expressing CPE receptors claudin-3 and claudin-4. Unfortunately, the utility of CPE is precluded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 19 publications
2
53
1
Order By: Relevance
“…Other in vivo studies of external therapeutic application of recombinant CPE also reported strong necrosis in the tumor tissues. 33,[35][36][37] In conclusion, we report the successful tumor-targeted CPE gene therapy in vitro and in vivo. This approach efficiently eradicates tumor cells, and provides an attractive therapeutic option for the potential local treatment of refractory solid tumors (including unresectable tumor lesions, residual tumors or recurrences), originating from colon, mammary, pancreas or prostate cancer, which overexpress claudin-3 or -4.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Other in vivo studies of external therapeutic application of recombinant CPE also reported strong necrosis in the tumor tissues. 33,[35][36][37] In conclusion, we report the successful tumor-targeted CPE gene therapy in vitro and in vivo. This approach efficiently eradicates tumor cells, and provides an attractive therapeutic option for the potential local treatment of refractory solid tumors (including unresectable tumor lesions, residual tumors or recurrences), originating from colon, mammary, pancreas or prostate cancer, which overexpress claudin-3 or -4.…”
Section: Discussionmentioning
confidence: 67%
“…Application of recombinant CPE protein leads to the dose-dependent rapid eradication of claudin-4-or claudin-3-overexpressing pancreas, breast or colon cancer cells in vitro and in vivo. 17,18,[33][34][35][36][37] The intratumoral in vivo application of recombinant CPE did not induce toxinassociated side effects, supporting its great therapeutic potential. However, these approaches require repeated, almost continuous regional or loco-regional application of recombinant CPE at doses ranging from 0.5 to 1.0 mg CPE per application to achieve therapeutic effects.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…18 -21 This further underscores a role for claudin EL domains in the formation and maintenance of TJ barriers and suggests a pharmacological approach to transiently increase paracellular permeability. [22][23][24] Although the specificity of CPE can be an advantage for this approach, 20,25 whether CPE interacts with other claudins is still being explored. The recent structural analysis of the CPE claudin binding site is an important step in determining the range of claudins other than claudin-3 and claudin-4 with the ability to interact with CPE.…”
mentioning
confidence: 99%
“…14,15) Furthermore, administration of Clostridium perfringens enterotoxin (cPE), whose receptor is cL-3 and cL-4, showed antitumor activity. [16][17][18] Because cL-4 is highly expressed in the epithelium covering mucosal immune tissues, the delivery of antigen to these tissues using a cL-4 ligand may lead to the development of mucosal vaccines. 19) Therefore cLs are very attractive as targets for drug delivery.…”
Section: Introductionmentioning
confidence: 99%